ANALISA KISAH IBRAHIM DALAM AL-QUR’AN PERSPEKTIF HERMENEUTIKA - Sahab, Muhammad Amin (Program Studi Ilmu Al-Qur'an dan Tafsir, Universitas Islam Negeri Datokarama Palu, 2024)
he Qur'an was revealed to the prophet Muhammad which is the greatest miracle and will not run out of time. The relevance of human life in the past or in the future is contained therein. Various kinds of art for understanding are presented in hermeneutics including understanding the substance of the Qur'an which can broaden one's horizons. There are many benefits in hermeneutics, but harm can also be obtained if there is an element of pragmatism. Therefore, this article seeks to analyze the story of Abraham in the Koran from a hermeneutical perspective. This article shows that the series of events experienced by Ibrahim are relevant to one another, if one looks at it at a glance that Abraham's struggle to awaken his people by being burned alive and sent to slaughter Ismail, then these events provide an opportunity for our mindset that the series this event was a test for Abraham in preaching patiently, sincerely, obediently, submissively and submissively to what Allah wills, immediately Allah's help immediately came and because of that Ibrahim received a high degree.